Determinan Audit Delay Pada Perusahaan Transportasi Indonesia - Yeney Widya Prihatiningtias; Febriana Putri Lestyadi (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to determine the factors causing audit delays involving the independent variables of profitability, solvency, operational complexity, audit opinion, and auditor reputation. The data include the annual financial reports of transportation companies listed on the Indonesia Stock Exchange between 2019 and 2021. The samples, selected through purposive sampling, include 37 companies accumulated into 111 within 3 years of observation and are analyzed by multiple panel data method. The test results exhibited that profitability, solvency, and auditor reputation had no significant effect on audit delay; and operational complexity and audit opinion had a negative effect on audit delay. The theoretical implications of this study are expected to provide contribution for audit delay research literature, and the practical implication suggest that transportation companies pay attention to significant variables such as audit opinion to further improve the performance of their financial statements, and OJK policies are expected to apply strict sanctions for companies submitting their financial reports after 90 days.